Contribution to the History of Janjevo in the Period of Socialism (1945–1991): Case Study "Oral History Kosovo" - Miketić, Uroš D. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
During the socialist era, Janjevo remained a small settlement with a predominantly Croat population. However, after World War II, due to the socio-political climate in Kosovo, many Croats increasingly migrated to Croatia. At the same time, Albanians and Roma immigrated en masse. Administratively, Janjevo held the status of a municipality after the war, but in 1961 it was incorporated into the municipality of Lipljan. This change in status limited its developmental prospects. The settlement and its population inherited significant Ottoman influences—visible in architecture, language, clothing, and other aspects—and there was ongoing cultural interaction among Janjevo’s residents of different nationalities. Daily life in Janjevo, particularly within the Croat community, was firmly centered around work and religion. Families were large and deeply devout, with the Catholic Church exerting considerable influence over nearly every aspect of communal life. A traditional patriarchal worldview prevailed, in which men were seen as breadwinners and women as caretakers of children and the household. General awareness of the importance of education and healthcare remained low, which significantly limited Janjevo’s developmental potential. Economic development in Janjevo was based on the operations of the “Metalac” factory and the nearby “Kišnica” mine, but above all on the vigorous growth of private entrepreneurship, largely led by Croats. During the 1980s, the local economy experienced a sharp decline, accompanied by rising interethnic tensions and a deepening national economic crisis. Interethnic relations in Janjevo were generally good, shaped by a broader environment that had inherited a culture of coexistence. However, the rise of Albanian nationalism and separatist movements placed increasing pressure on Croats to emigrate, gradually altering the ethnic composition of the settlement in favor of the Albanian population. Croats traditionally respected Serbia as their mother republic, but this relationship began to deteriorate during the 1980s, amid escalating tensions along the Belgrade–Zagreb axis. The Croatian government invested economically in Croat-populated areas of Kosovo and even considered the collective relocation of Kosovo Croats to Croatia.